2013
DOI: 10.1002/grl.50522
|View full text |Cite
|
Sign up to set email alerts
|

Variability of central United States April–May tornado day likelihood by phase of the Madden‐Julian Oscillation

Abstract: April–May tornado day likelihood from 1990 to 2011 was calculated for the central United States for phases of the Madden‐Julian Oscillation (MJO). An April tornado day was found more likely during MJO phases 6 and 8 and less likely during phases 3, 4, and 7. A May tornado day was found more likely during phases 5 and 8 and less likely in phases 2 and 3. During phases with above‐normal tornado day likelihoods, positive anomalies of convective available potential energy, bulk vertical wind shear, and storm‐relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 40 publications
7
56
0
Order By: Relevance
“…e mean and mean rank of the tornado counts was greatest with phase 4 in MAM. Clustering of tornadoes on MJO phase 4 days in MAM is unique because climatological studies [20,23] that aggregated data over a larger number of seasons reported heightened tornado activity with phase 2, 5, and 7 of the MJO in boreal spring months. While only representative of MAM 1982 and 1983, the clustering of tornadoes on MJO phase 4 days in these EN seasons highlights the possibility for a large number of tornadoes when subseasonal climate oscillations are in unfavorable phases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…e mean and mean rank of the tornado counts was greatest with phase 4 in MAM. Clustering of tornadoes on MJO phase 4 days in MAM is unique because climatological studies [20,23] that aggregated data over a larger number of seasons reported heightened tornado activity with phase 2, 5, and 7 of the MJO in boreal spring months. While only representative of MAM 1982 and 1983, the clustering of tornadoes on MJO phase 4 days in these EN seasons highlights the possibility for a large number of tornadoes when subseasonal climate oscillations are in unfavorable phases.…”
Section: Discussionmentioning
confidence: 99%
“…e MJO is a tropical wave of enhanced convection that propagates the globe from west to east at approximately 5 m·s −1 [29]. It is linked to variability in tornado activity in the midlatitudes through changes in global relative atmospheric angular momentum (AAM), which arise from tropical convective forcing and teleconnected Rossby wave propagation in the midlatitudes [20,23,[30][31][32]. Other factors, such as friction and mountain torque, affect AAM in addition to tropical convection [30][31][32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The index is created such that the MJO generally progresses eastward, from phase 1 to 8 and back to phase 1 again. Days during which the magnitude of the MJO vector was less than one standard deviation from zero were not considered, following the compositing methodology of other recent studies (e.g., Zhou et al 2012;Virts et al 2013;Zhang 2013;Barrett and Gensini 2013). Anomalies in daily DSIC, 500-hPa geopotential height, sea level pressure, 2-m air temperature, and 10-m wind were then found by averaging the day n means for each MJO phase and subtracting them from the overall monthly mean.…”
Section: Methodsmentioning
confidence: 99%